Chapter 5.16 Research Management and Administration in Vietnam - Dao Thanh Truong; Nguyen Thi Quynh Anh (Emerald Publishing Limited, 2023)
This chapter outlines the structure of research management and administration (RMA) in Vietnam, which is a part of the science and technology management sector. The chapter will present the decentralisation of RMA in Vietnam at many levels: the macro level (state), the medium level (local/province), and the micro level (organisations); describe its characteristics, and identify the conditions for the establishment of the RMA community in Vietnam shortly.
10.1108/978-1-80382-701-820231050; 10.1108/978-1-80382-701-820231050; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262